2013
DOI: 10.1016/j.ibmb.2013.09.007
|View full text |Cite
|
Sign up to set email alerts
|

A 104 kDa Aedes aegypti aminopeptidase N is a putative receptor for the Cry11Aa toxin from Bacillus thuringiensis subsp. israelensis

Abstract: The Cry11Aa protein produced in Bacillus thuringiensis subsp. israelensis, a bacterial strain used worldwide for the control of Aedes aegypti larvae, binds midgut brush border membrane vesicles (BBMV) with an apparent Kd of 29.8 nM. Previously an aminopeptidase N (APN), named AaeAPN2, was identified as a putative Cry11Aa toxin binding protein by pull-down assays using biotinylated Cry11Aa toxin (Chen et al., (2009) Insect Biochem Mol Biol., 39: 688–696). Here we show this protein localizes to the apical membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 42 publications
2
60
0
Order By: Relevance
“…Similarly, cadherins in seven lepidopteran, two dipteran, and two coleopteran species have been confirmed or suggested to be receptors for other Cry toxins (2,(12)(13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Similarly, cadherins in seven lepidopteran, two dipteran, and two coleopteran species have been confirmed or suggested to be receptors for other Cry toxins (2,(12)(13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 89%
“…Until now, insect cadherins have been proven or suggested to interact with Cry toxins in at least six lepidopteran (2), two dipteran (12)(13)(14), and two coleopteran (15,16) species. A toxin-binding cadherin receptor is composed of five domains: signal peptide (SP), 8 to 12 cadherin repeats (CRs), membrane-proximal extracellular domain (MPED), transmembrane region (TM), and internal cytoplasmic domain (IC) (17).…”
mentioning
confidence: 99%
“…Functional studies have turned midgut CAD-like proteins into one of the most likely Cry toxin receptor molecules in lepidopteran, dipteran, and coleopteran larvae (7,12,38). It has been proposed that they play the role of the first receptor of Cry toxins, binding toxin monomer and facilitating further processing required for the prepore oligomer formation (17).…”
Section: Discussionmentioning
confidence: 99%
“…Although Cry toxins share a similar mechanism of action, different Cry-binding molecules (receptors), such as cadherin Chen et al, 2009), aminopeptidase (Abdullah et al, 2006;Zhang et al, 2008), alkaline phosphatase (Fernandez et al, 2006) and α-amylase (Fernandez-Luna et al, 2010) have been identified in mosquito species. A previous work (Beltrão & Silva-Filha, 2006) has shown that Cry toxins may share a class of binding sites when competition assays were carried out.…”
Section: Toxicity Analysis Of Cry4aa and Cry4ba To A Aegypti Larvaementioning
confidence: 99%